'We are the bridge': an implementation research study of SEWA Shakti Kendras to improve community engagement in publicly funded health insurance in Gujarat, India. (15th November 2022) - Thomas, Susan; Sivaram, Sharmada; Shroff, Zubin; Mahal, Ajay; Desai, Sapna
Abstract : Introduction: India's efforts towards universal health coverage include a national health insurance scheme that aims to protect the most vulnerable from catastrophic health expenditure. However, emerging evidence on publicly funded health insurance, as well as experience from community-based schemes, indicates that women face specific barriers to access and utilisation. Community engagement interventions have been shown to improve equitable utilisation of public health services, but there is limited research specific to health insurance. We examined how existing community-based resource centres implemented by a women's organisation could improve women's access to, and utilisation of, health insurance. Methods: We conducted an implementation research study in Gujarat, India to examine how SEWA Shakti Kendras, established by the Self-Employed Women's Association, worked to improve community engagement in health insurance. SEWA organises women in the informal sector and provides social protection through health, insurance and childcare services. We examined administrative data, programme reports and conducted 30 in-depth qualitative interviews with users and staff. Data were analysed thematically to examine intervention content, context, and implementation processes and to identify enablers and barriers to improving women's access to health insurance through SEWA's community engagement approach. Results: The centres worked through multiple channels—doorstep services, centre-based support and health system navigation—to strengthen women's capability to access health insurance. Each centre's approach varied by contextual factors, such as women's digital literacy levels and rural–urban settings. Effective community engagement required local leadership, strong government partnerships and the flexibility to address a range of public services, with implementation by trusted local health workers. Conclusion: SEWA Shakti Kendras demonstrate how a local, flexible and community-based model can serve as a bridge to improve utilisation of health insurance, by engaging women and their households through multiple channels. Scaling up this approach will require investing in partnerships with community-based organisations as part of strategies towards universal health coverage.